Extraction and Characterization of Melanin Nanoparticles from Gallus gallus domesticus Feathers - Iqra Bule; Anzalna Momin; Kantilal Nagare; Dinesh Wanule (The Bioscan, 2025)
Melanin, a multifunctional biopolymer naturally found in birds, has demonstrated significant potential as a reducing agent. This study reports the extraction and characterization of melanin nanoparticles derived from the waste feathers of domestic chickens (Gallus gallus domesticus). Melanin was extracted using an acid-base method, confirmed through UV-Vis spectroscopy, thin-layer chromatography (TLC), and transmission electron microscopy (TEM). The pigment exhibited a characteristic peak at 230 nm in UV spectroscopic analysis, an TLC exhibit the Rf value of melanin is 0.67, and Transmission electron microscopy reveals the melanin nanoparticle breadth of 315 nm and had elongated shape with rough-surface area. Its reducing ability was validated through a Methylene Blue Reduction Test (MBRT).